Edukasi Kesehatan Mental pada Ibu Hamil dan Postpartum (Lembaga Pengembangan Kinerja Dosen, 2025)
Maternal mental health is an important aspect during pregnancy and postpartum, which has a significant impact on both mother and baby. There are various psychological problem that may occur during pregnancy and the postpartum stage due to the physical and psychological changes that occur. In addition, a woman also adapt as her new role as s new parent. The purpose of this community service is an effort to increase the knowledge of pregnant and postpartum woman to minimize the occurrence of mental health disorders. This community activity method with socialization on mental health education for pregnant women and postpartum was held on May 15, 2023, at the Melati Posyandu Gunungjati Village, this program is aimed at pregnant women in first and third trimesters, the number of participants who attended was 16 people. Assessment of mother’s knowledge about mental health with pre-test and post-test. The result of socialization were analyzed by approaching descriptively, proving that with the educational provisions that have been provided, new knowledge can be added.